Pengaruh Pembelajaran Flipped Classroom terhadap Hasil Belajar Prosedural pada Konteks Mata Pelajaran Pemrograman Dasar Program Keahlian Teknik Komputer dan Jaringan di SMK Negeri 3 Malang - Zahrotul Indah Mulyasari; Admaja Dwi Herlambang; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The background of this research is the recovery after the Covid-19 pandemic which requires that students' learning and teaching activities must be carried out in a limited manner. Teaching teachers feel the need to review material that has been discussed during online (online) learning, so that the time needed during practicum sessions is reduced. Students are not able to understand the material properly, causing their learning outcomes to decrease. This study aims to find out whether the flipped classroom learning model can have an impact on procedural learning outcomes in Basic Programming subjects at SMK Negeri 3 Malang. The approach used is a quantitative approach, a Quasi-Experimental research type with a control-group pretest posttest design. The samples taken in this study were students of class X TKJ with a total of 40 students. Student learning outcomes were tested using the Unpaired Sample T-test and the N-Gain test. The results of the Unpaired Sample T-test show that the flipped classroom learning model has a positive influence on students' procedural learning outcomes, while the learning outcomes tested using N-Gain increase the average on student learning outcomes from the initial average of 29.333 with interpretation